Analysis of enteric pathogenicity of multidrug-resistant Pseudomonas spp. isolated from commercial UHT milk - Saha, Bishakha Joyeeta (2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.